PENGGUNAAN HYDRO-CRACK SYSTEM SEBAGAI UPAYA MENINGKATKAN KINERJA MESIN - Winoko Agus Yuniarto; Hertomo Bambang; Nurhadi Nurhadi (ROTOR, 2018)
The use of hydro-crack systems in combustion motors in addition to functioning to improve exhaust emissions and improve engine performance through the combustion process. Perfect combustion can be adjusted during the combustion process. The purpose of the study was to determine the select magnitude of power increase, decrease fuel consumption and increase the average effective pressure and rotation of the use of 92 octane fuel without HCS. The method of testing engine performance in obtaining data is constant speed (v boarding) based on ISO 1585. Subsequent data signifies presented in a graphical form which is then calculated by statistics. Power increased 2.83hP and bmep 43.19kPa at 4000rpm, sfc dropped 0.0358kg / hP. Hours at 1000rpm and rose by 43.19kPa, when using 92 octane fuel against the standard. When using octane 95 with HCS the power rises 7.95hP at 4000rpm, buys 28.42 kPa when 4500 and sfc drop 0.0537kg / hp. Hours at 1000rpm Keywords: power, fuel consumption, effective average pressure, octane value, hydro-crack system